2019
DOI: 10.1111/jocd.13149
|View full text |Cite
|
Sign up to set email alerts
|

Stromal vascular fraction‐enriched platelet‐rich plasma therapy reverses the effects of androgenetic alopecia

Abstract: Background Since antiquity, humans have been trying to devise remedies to cure androgenetic alopecia (AGA). These efforts include use of oral and topical concoctions and hair transplant strategies. As AGA affects people of all colors and creed, there has been a continuous effort to find a magic bullet against AGA. Unfortunately, to date, all the strategies to negate AGA effects have limitations and thus require new treatment options. Aim To evaluate the efficacy of use of stromal vascular fraction (SVF) in and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 18 publications
2
39
1
Order By: Relevance
“…Adipose tissue has an important place in both tissue engineering and regenerative medicine applications as a biological active complex. Adipose tissue can be used either directly as SVF or as stem cell separated from SVF [21]. In our study, we used SVF, which contains stem cell, directly.…”
Section: Discussionmentioning
confidence: 99%
“…Adipose tissue has an important place in both tissue engineering and regenerative medicine applications as a biological active complex. Adipose tissue can be used either directly as SVF or as stem cell separated from SVF [21]. In our study, we used SVF, which contains stem cell, directly.…”
Section: Discussionmentioning
confidence: 99%
“…There was also significant improvement in the physician and patient assessment scores in the SVF-PRP group. 39 A similar study by Stevens et al also reported benefits with the combined therapy of SVF with PRP (platelet-rich stroma [PRS]) 40 …”
Section: Stromal Vascular Fractionmentioning
confidence: 96%
“…There was also significant improvement in the physician and patient assessment scores in the SVF-PRP group. 39 A similar study by Stevens et al also reported benefits with the combined therapy of SVF with PRP (platelet-rich stroma [PRS]) 40 Several studies are available for ADSC-CM using commercial ADSC-CM products called advanced adipose-derived stem cell protein extract (AAPE ) (Prostemics Co, Ltd, Seoul, South Korea) by Fukuoka et al who studied 68 patients of male and female pattern hair loss (PHL) over 5 years in three published studies. [41][42][43][44] ADSC-CM was found to be effective in inducing hair growth.…”
Section: Stromal Vascular Fractionmentioning
confidence: 99%
“…Moreover, many studies proved that ADSCs favor the bulb function by stimulating hair follicle stem cells (HFSCs) [17][18][19][20][21][22][23]. The association of SVF and platelet-rich plasma (PRP) has proved to be an effective protocol in the treatment of androgenetic alopecia but the standard protocol of autologous regenerative treatment for AGA involves the injection of microfragmented adipose tissue in the scalp [24,25]. We limited this approach to cases of Secondary Cicatricial Alopecia (SCAs), where the engraftment of mature adipocytes was useful in order to recreate or enhance subdermal thickness [26].…”
Section: A Clear Target and A Novel Therapymentioning
confidence: 99%